Levantine vignettes : an educator's account of border crossing in the Middle East - Osborn, Daniel (Research in life writing and education, 2024)
"In the United States, the dominant perception of the Middle East is that the region is defined by violence, conflict, and extremism. This narrative erases the humanity and dignity of the region's communities and perpetuates Orientalist myths about backwardness, inferiority, and a class of civilizations. Levantine Vignettes is the account of one history educator and his lifelong journey to appreciate the vibrancy, vitality, diversity, and dynamism of the Middle East through the embodied learning that emerges through travel and cultural immersion. Following Daniel Osborn from his first trip to Israel as an undergraduate student through his Peace Corps service in Jordan and well beyond, Levantine Vignettes demonstrates the transformative power of working with and living among communities in Israel, the Palestinian West Bank, Jordan, and Lebanon. From harvesting and planting olive trees to herding livestock in the desert, this account provides a glimpse into the process of becoming a global educator committed to crossing borders and cultivating compassion through knowledge"--